Шелк: [роман] / Алессандро Барикко ; [перевод с итальянского Г. Киселева] - Барикко Алессандро (Азбука-классика, 2010)
Экземпляры: аб. (20200123) / Инвентарный номер: 59954 / Цена: / Сис.шифр: 84(4Ита)-4 / Авт.знак: Б 24 / ГРНТИ: 17.82.31 / ББК: 84(4Ита)-44